Back Cover: Amino Acid Oxidation: A Combined Study of Cysteine Oxo Forms by IRMPD Spectroscopy and Simulations (Chem. Eur. J. 48/2016). Issue 48 (2nd November 2016) - Scuderi, Debora; Bodo, Enrico; Chiavarino, Barbara; Fornarini, Simonetta; Crestoni, Maria Elisa
Abstract : Redox signaling is triggered by post‐translational modifications at the cysteine thiol target. Cysteine residues in sulfenic, sulfinic and sulfonic forms are key intermediates in the redox‐switch chemistry of proteins. The deprotonated species were thoroughly characterized by an integrated approach combining tandem mass spectrometry, action IR spectroscopy and ab initio molecular dynamics simulations. Vibrational signatures mark the progressive cysteine sulfur oxidation and modulation of the deprotonation site (from carboxylic group in cysteine sulfenic acid to sulfonic group in the highest oxidized species). More information can be found in the Full Paper by M. E. Crestoni et al. onpage 17239 ff.